New approach allowing detection of Cl using a pulsedcarbon dioxide (CO2) laser-induced breakdown spectroscopy (LIBS). Issue 1 (February 2021) - Sari, A M; Lahna, K; Ramli, M; Miura, A; Kurihara, K; Marwan; Idris, N
Abstract: A new approach to allow detection of Cl emission using atransversely excited atmosphere (TEA) carbon dioxide (CO2 ) laser-induced breakdown spectroscopy (LIBS), namely utilization of a metal sub-target, was introduced. The Cl sample was prepared from pure chemical powder in the form of a solutiondeposited on the metal sub-target. A zinc selenium lens was used to focus the CO2 laser beam (10.6Mm, 2.5 J, 10 Hz, 200 ns) onto the deposited sample under the surrounding gas of helium (pressure of 1 atm) for generated luminous plasma. An optical multichannel analyzer (OMA) system was used for collecting plasma and acquiring the emission spectrum. It was found that luminous plasma can be produced upon focusing the laser irradiation onto the deposited layer of the sample on the subtarget metal while leaving no ablation from the sub-target metal. Many ionic emission lines from Cl can be detected in the visible region.The ionic emission lines occur withfavorable spectrochemical features, namely strong emission intensity and low background level. Thus, this new approach is promising for conducting Cl analysis using a CO2 LIBS.